Upaya Peningkatan Akivitas dan Hasil Belajar Siswa Melalui Media E-Book Berekstensi Epub - Miftahul Hakim; Haning Hasbiyati (FKIP Universitas Islam Jember, 2018)
At present, technological progress is very rapid, including the advancement of smartphone use. Based on the results of observations of biology subjects the majority of students are passive, students feel saturated with conventional methods, students still depend on the delivery of material delivered by the teacher. Therefore, researchers used smartphones as a medium to support the learning process. This study used action research (PTK) design. The data were collection using quantitative tests of cognitive learning outcomes, qualitative observations and documentation files. The subjects of this study were 22 students. Based on the observations of the activities of students in cycles 1 and 2 there was an increase from 65.9% to 73.9% of active criteria, with an increasing percentage of 8%. learning outcomes were improved in cycles 1 and 2: cycle 1 (pretest) 36.8%, (post-test) 64.9%. the improvement of learning outcomes in cycle I and 2 was 4.3%, according to the results of the first cycle cognitive gain score test obtained 0.44 in medium criteria, the results of the second cycle cognitive gain score test obtained 0.45 in medium criteria. The improvement of cognitive test was 0.01. Based on these comparisons, it was concluded that E-Book media with EPUB extension could improve student learning activities and outcomes. Keywords: learning activity, learning outcome, e-book with epub extension